Titanium thiosalicylate complexes: functional metalloligands for the construction of redox-active heterometallic architectures12. Issue 43 (11th October 2018) - Fandos, Rosa; Bruña, Sonia; Hernández, Carolina; Otero, Antonio; Rodríguez, Ana; Ruiz, María José; Terreros, Pilar; Cuadrado, Isabel
Abstract : A new versatile titanium metalloligand for the synthesis of redox active d 0 –d 8 heterometallic complexes. Abstract : The titanium complex [TiCp*(thiosal)(thiosalH)] (1 ) has been synthesised by reaction of [TiCp*Me3 ], Cp* = η 5 -C5 Me5, with thiosalicylic acid (H2 thiosal). Complex1 reacts with [M(μ-OH)(COD)]2 (M = Rh, Ir) to yield the corresponding early–late heterobimetallic complexes [TiCp*(thiosal)2 M(COD)] (M = Rh (2 ); Ir (3 )). Carbon monoxide replaces the COD ligand in2 and3 leading to the respective dicarbonyl complexes [TiCp*(thiosal)2 M(CO)2 ] (M = Rh (4 ); Ir (5 )). Compound4 reacts with PPh3 to yield the monocarbonyl derivative [TiCp*(thiosal)2 Rh(CO)(PPh3 )] (6 ). The reaction of compound1 with Li n Bu yields the tetrametallic complex [TiCp*(thiosal)2 Li2 (THF)3 (H2 O)] (7 ). Compound7 reacts with [RuCp*Cl(COD)] yielding the heterometallic complex [TiCp*(thiosal)2 RuCp*] (8 ). The molecular structures of compounds4, 5 and7 have been studied by X-ray diffraction. From cyclic voltammetric (CV) and square wave voltammetric (SWV) experiments, we observed that attachment of the titanium moiety of precursor1 to a late transition metal moiety through the sulfur atoms has a significant influence on the reduction behaviour of the Ti(iv ) metal centre. Thus, monometallic1 exhibits an irreversible reduction process at −1.15 V vs. SCE, whereas the CVs of heterobimetallic compounds2–6 are characterized by the reversible or quasi-reversible one-electron reduction of the Ti(iv )/Ti(iii ) system, suggesting a significant stabilization of the Ti(iii ) reduced species. Likewise, substitution of the M(COD) diolefin fragment in2 and3 by the M(CO)2 carbonyl-containing moiety (in compounds4 and5 ) leads to a significant anodic shift in the titanium E 1/2 reduction redox potentials.